Implementasi Model Pembelajaran Discovery Learning dalam Meningkatkan Keaktifan Belajar Siswa Pada Mata Pelajaran PAI - Andriyani, Ani; Ismawati, Iis; Hadijah, Ifah; Dyah Ariyani, Wiwik (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
This study aims to analyze the implementation of the Discovery Learning model in improving student learning activeness in Islamic Religious Education (PAI) subjects. The background of this study is the low level of students' active participation in the Islamic Education learning process, which is often one-way. The Discovery Learning model was chosen because it has the potential to stimulate students to discover concepts and principles independently, so it is expected to increase their involvement and understanding. The research method used was descriptive qualitative with a qualitative approach. The research subjects were fifth grade students at SDN 050 Cibiru who were the object of the implementation of the Discovery Learning model in PAI learning. Data were collected through direct observation in the classroom, interviews with PAI teachers, and document analysis related to the learning process. The results showed that the implementation of the Discovery Learning model can significantly increase students' learning activeness in PAI subjects. Students look more enthusiastic, dare to ask questions, discuss, and seek their own information to solve problems or understand the material. This can be seen from the increase in student interaction with teachers and fellow students, as well as internal motivation to learn. The obstacles found include students' initial adaptation to the new learning model and the need for more careful teacher preparation in designing learning scenarios. The conclusion of this study is that the Discovery Learning learning model is effective in increasing students' learning activeness in PAI subjects. It is recommended for PAI teachers to consider this model as one of the innovative and student-centered learning strategies.